CONTENT MARKETING STRATEGIES IN INCREASING CONSUMER INTERACTIONS WITH SOCIAL MEDIA USERS - Wardani, Risma; Rasidi, Rasidi; Widia, Ayu; F, Cahya; Aisyah, Dita; Nafisah, Dela; Khaira, Muftihatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article discusses Content Marketing Strategies in Increasing Consumer Interaction with Social Media Users. In Indonesia, the number of active social media users will be 167 million people in January 2023. This number is equivalent to 60.4% of the population in the country. The large number of active social media users in Indonesia today has an impact on the development of the digital economy. Trends in the business world continue to vary towards digitalization and have succeeded in changing the way we interact in marketing communications from conventional marketing to digital marketing. The basic motivation behind digital marketing is to advance the brand, form preferences and increase sales through several digital marketing promotional methods such as content marketing. The objectives to be achieved in this research are to understand content marketing strategies in increasing consumer interaction with social media users and analyzing factors. drivers and barriers in increasing consumer interaction with social media users through content marketing. This research uses a qualitative approach with a case study type of research. Data collection was carried out by observation, interviews and documentation. The results of this research show that the content marketing strategy for increasing consumer interaction among social media users is to create content that is easy to understand, share motivation, persuade and encourage customers, explain product supporting criteria, and pay attention to the views of friends, family and the surrounding environment. The driving and inhibiting factors in increasing consumer interaction with social media users through content marketing are through design, presenting the latest phenomena, consistency in uploading, and suitability for customers.